An Examination of Michigan State University's Image Repair via Facebook and the Public Response Following the Larry Nassar Scandal. (February 2021) - Frederick, Evan; Pegoraro, Ann; Smith, Lauren Reichart
The purpose of this study was to examine how Michigan State University (MSU) utilized Facebook as a tool for image repair following the Larry Nassar sex abuse scandal. Specifically, the researchers were concerned with the image-repair approach utilized by MSU during Nassar's hearing and in its immediate aftermath. Additionally, the researchers examined users' responses via Facebook comments to determine reactions to MSU's image-repair strategies. MSU primarily employed the image-repair tactic of corrective action along with rallying, bolstering, and mortification. Overall, individuals posting comments did not appear to buy into MSU's image repair. Users focused blame on MSU for mishandling the situation and discussed various aspects of the Nassar case as well as MSU's mistreatment of the victims. Additionally, there was a call for MSU to change its culture, take ownership of its mistakes, and become a leader in dealing with sexual assault on campus.